가축 기호성이 높은 내탈립 삼차망 청보리 신품종 ‘유호’ - 박태일(Tae-Il Park); 서재환(Jae-Hwan Seo); 한옥규(Ouk-Kyu Han); 김경훈(Kyeong-Hun Kim); 박기훈(Ki-Hun Park); 오영진(Young-Jin Oh); 최재성(Jae-Seong Choi); 박종철(Jong-Chul Park); 박형호(Hyoung-Ho Park); 김홍식(Hong-Sik Kim); 김정곤(Jung-Gon Kim); 송태화(Tae-Hwa Song); et al. (Korean journal of breeding, 2011)
청보리 신품종 '유호'는 까락이 없어 가축 기호성이 높지만 수확 시 곡실의 탈립이 많아 수량 및 영양적 손실이 큰 기존 삼차망 품종 '유연'의 단점을 개선하기 위하여 1999년에 내탈립 삼차망인 수원339호를 모본으로 하고, 보리호위축병에 강하고 총체적성에 좋은 수원355호를 부본으로 교잡하여 계통육종법에 의하여 제반 특성이 우수한 'SB992047-B-B-B-6-2' 계통을 선발, 생산력검정시험과 지역적응시험을 거쳐 2008년에 육성되었다. 그 특성을 Youho' (Hordeum vulgare L.), a new ruminant-palatable forage barley cultivar, was developed by the breeding team at the Department of Rice and Winter Cereal Crop, National Institute of Crop Science, RDA in 2008. It was derived from the cross between 'Suwon339' and 'Suwon355'. Among the cross made in 1999, a promising line, SB992047-B-B-B-6-2, showed good characteristics in potential forage yield in the yield trial tested at Iksan from 2005 to 2006. In 2007, it was designated as 'Iksan431' and placed in regional yield trials at eight locations in Korea for two years from 2007 to 2008, and was released as the name of 'Youho'. It has the growth habit of group II, erect plant type, green leaf and hood spike. Its average heading and maturing dates were on Apr. 24 and May 26, respectively, which are similar to check cultivar 'Yuyeon'. 'Youho' also showed weaker winter hardiness, but better resistance to lodging, shattering and BaYMV than those of check cultivar. It showed higher crude protein content, grade of silage quality than those of check cultivar. The average forage dry matter yield in the regional yield trial was about 14.1, 10.9 MT ㏊ -1 in upland and paddy field, respectively, which were 1% to 4% lower than that of the check cultivar. This cultivar would be suitable for the area whose daily minimum temperature was above -8℃ in January in Korean peninsula.